2019
DOI: 10.1002/jcb.28839
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide regulates oxidative stress‐induced mitophagy and suppresses apoptosis through p53 signaling pathway in C2C12 myoblasts

Abstract: Muscle redox disturbances and oxidative stress have emerged as a common pathogenetic mechanism and potential therapeutic intervention in some muscle diseases. Parthenolide (PTL), a sesquiterpene lactone found in large amounts in the leaves of feverfew, possesses anti‐inflammatory, anti‐migraine, and anticancer properties. Although PTL was reported to alleviate cancer cachexia and improve skeletal muscle characteristics in a cancer cachexia model, its actions on oxidative stress‐induced damage in C2C12 myoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…In this regard, Gopal et al have reported that PN can stimulate the ubiquitination of MDM2 thereby activating p53 cellular functions [ 83 ]. More recently, activation or stabilization of p53 by PN in tumor cells has also been found by other authors [ 17 , 84 , 85 ].…”
Section: The Effect Of Parthenolide On Gene Expression Profilesupporting
confidence: 74%
See 1 more Smart Citation
“…In this regard, Gopal et al have reported that PN can stimulate the ubiquitination of MDM2 thereby activating p53 cellular functions [ 83 ]. More recently, activation or stabilization of p53 by PN in tumor cells has also been found by other authors [ 17 , 84 , 85 ].…”
Section: The Effect Of Parthenolide On Gene Expression Profilesupporting
confidence: 74%
“…Indeed, patients often develop a wasting syndrome characterized by systemic inflammation and involuntary loss of body mass that cannot be reversed by normal nutritional support [ 15 ]. NF-κB inhibitors could also be used as anticancer therapy to treat cachexia [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The net effect of these pathways is both energy generation and biosynthesis of macromolecules for proliferation. DMAPT has been shown to directly inhibit cell survival and proliferative signals from nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐κB), 34,40 signal transducer and activator of transcription (STAT), 44 and mitogen‐activated protein kinases (MAPK) 45 . At the same time, DMAPT activates proapoptotic signaling through c‐Jun N‐terminal kinases (JNK) and p53 33,34,46 .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is no widely accepted in vitro model for migraine. Both C2C12 myoblasts and meningeal mast cells [35] have been used as model for migraine research [36]. Harriott et al also suggested the spreading depression model to be used as a preclinical model of migraine [37].…”
Section: Discussionmentioning
confidence: 99%